Multiletramentos e multimodalidade: o design de significados em livros didáticos de língua portuguesa e inglesa - Mecca, Édina Menegat (2019)
The theme of this study is the multiliteracies and its delimitation is the meaning designed in multimodal genres through reading activities in Portuguese and English language textbooks. The aim of this study is to analyse the activities for the design of meaning in multimodal texts suggested in these books in order to check their contribution for the promotion of multiliteracies. Through this objective, the theoretical background is connected to the studies of Bakhtin (2016) about discursive genres and dialogism; Chartier (1994), Petit (2008) and Kleiman (2004, 2005, 2014) when it comes to reading practices; Kress (2000, 2010, 2014) and Kress and van Leeuwen (2006) regarding multimodality; as well as The New London Group (2000), Lemke (2010) and Rojo (2012, 2013) in reference to multiliteracies. The corpus consists of reading activities of four multimodal texts from the textbooks “Português: Linguagens”, by Cereja and Magalhães (2015), and "Way to English", by Franco and Tavares (2015), both designed for the sixth year of elementary school. It has been observed that these textbooks promote the multiliteracies by considering the design of meaning intrinsec to multimodal communication. It has also been verified that relevant aspects are ignored by these reading activities when it comes to the visual design. For that reason, complementary questions based on the grammar of visual design, by Kress and van Leeuwen (2006), were suggested for each multimodal text.